2017
DOI: 10.1186/s12889-017-4671-3
|View full text |Cite|
|
Sign up to set email alerts
|

Electronic cigarette use behaviors and motivations among smokers and non-smokers

Abstract: BackgroundThe use of electronic cigarettes (EC) has risen exponentially over the past decade, including among never smokers, and ECs are now the most popular tobacco product among teenagers in the US. While, EC manufacturers utilize numerous marketing strategies to target both smokers and non-smokers, it is unclear how perceptions and behaviors differ between these two groups.MethodsWe conducted a survey of 320 adults either via online surveys or in Baltimore vape shops to determine demographics, behaviors, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…Enjoyment and satisfaction may influence use of e-cigarettes and CTC [45][46][47][48][49] therefore both are critical to consider. In fact, among a sample of college students between the ages of 18 and 23 years, enjoyment surpassed all reasons for daily and non-daily e-cigarette use, including quitting or reducing smoking and decreasing craving [47].…”
Section: Craving Reduction Aversionmentioning
confidence: 99%
“…Enjoyment and satisfaction may influence use of e-cigarettes and CTC [45][46][47][48][49] therefore both are critical to consider. In fact, among a sample of college students between the ages of 18 and 23 years, enjoyment surpassed all reasons for daily and non-daily e-cigarette use, including quitting or reducing smoking and decreasing craving [47].…”
Section: Craving Reduction Aversionmentioning
confidence: 99%
“…Moreover, in 2015 and 2016, the results from two different national surveys show that 40% and 44%, respectively, of current e-cigarette users aged 18–C24 years were sole e-cigarette users [ 27 , 29 ]. E-cigarettes may be safer than cigarettes for smokers [ 30 ], but never smokers who use e-cigarettes likely receive little benefit [ 31 ]. Studies have shown that the perception of e-cigarettes and motivation for e-cigarette use varied based on cigarette smoking status [ 31 , 32 ], therefore, factors unique to never smokers need to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 an estimated 2291 adolescents in Great Britain (GB) aged 11-18 years used e-cigarettes (2). Although some reports suggest that regular use (once a week or more) amongst youth is rare and largely limited to current or previous smokers (2)(3)(4), awareness of and experimentation with e-cigarettes is rising (2,(5)(6)(7)(8). Similar trends have been noted in other countries including the USA and Canada (9,10).…”
Section: Introductionmentioning
confidence: 80%
“…This small scale mixed method study aimed to explore Welsh primary schoolchildren's (aged [7][8][9][10][11] awareness of e-cigarettes relative to tobacco smoking, their understanding of the risks and benefits associated with e-cigarettes and their intentions and beliefs about vaping; to inform development of effective prevention strategies and policy responses around e-cigarette use.…”
Section: Introductionmentioning
confidence: 99%